Edmodo as a solution to enhance student learning interest in high school biodiversity during the COVID-19 pandemic - Ervan Johan Wicaksana; Pramana Atmadja; W Wikanso; Loly Nadila Putri; Gusti Ayu Muthia (Biosfer: Jurnal Pendidikan Biologi, 2020)
This study aims to improve the quality of learning by applying Edmodo's application at biodiversity class material of class 10 students in increasing student learning interest during Covid-19 period. Based on observations at SHS 3 Kerinci regency in Jambi province, Indonesia it was known that students' interest in learning biology was still low. This was due to the lack of availability of existing facilities and the learning process that is still through lectures and questions and answers. Students were less involved in exploring information about biological concepts causing low student interest in learning. The method used was Classroom Action Research. The research procedure was in the form of a cycle to know the improvement of student interest. Each cycle consists of four stages, including Planning, Acting, Observation, and Reflection. Data Collection Techniques was conducted through Questionnaire, Observation, and Documentation. This data collection used an instrument in the form of an Online Learning Interest Questionnaire and Observation Sheet conducted online. This study showed that the results of observations of student interest in online learning obtained in cycle II received criteria of very high at 96%. While the results of student interest in online learning questionnaire obtained with high criteria that was 76.74%. Based on the research done, it can be concluded that the application of Edmodo media in online learning increases student interest in biodiversity material in science class X-2 SHS 3 Kerinci regency in Jambi, Indonesia.